Exploring NK cell receptor dynamics in paediatric leukaemias: implications for immunotherapy and prognosis - Cui Tu; Irina Buckle; Ingrid Leal Rojas; Gustavo Rodrigues Rossi; David P Sester; Andrew S Moore; Kristen Radford; Camille Guillerey; Fernando Souza‐Fonseca‐Guimaraes (Clinical & Translational Immunology, 2024)
Abstract Objectives Immunotherapies targeting natural killer (NK) cell receptors have shown promise against leukaemia. Unfortunately, cancer immunosuppressive mechanisms that alter NK cell phenotype prevent such approaches from being successful. The study utilises advanced cytometry to examine how cancer immunosuppressive pathways affect NK cell phenotypic changes in clinical samples. Methods In this study, we conducted a high‐dimensional examination of the cell surface expression of 16 NK cell receptors in paediatric patients with acute myeloid leukaemia and acute lymphoblastic leukaemia, as well as in samples of non‐age matched adult peripheral blood (APB) and umbilical cord blood (UCB). An unsupervised analysis was carried out in order to identify NK cell populations present in paediatric leukaemias. Results We observed that leukaemia NK cells clustered together with UCB NK cells and expressed relatively higher levels of the NKG2A receptor compared to APB NK cells. In addition, CD56dimCD16+CD57− NK cells lacking NKG2A expression were mainly absent in paediatric leukaemia patients. However, CD56br NK cell populations expressing high levels of NKG2A were highly represented in paediatric leukaemia patients. NKG2A expression on leukaemia NK cells was found to be positively correlated with the expression of its ligand, suggesting that the NKG2A‐HLA‐E interaction may play a role in modifying NK cell responses to leukaemia cells. Conclusion We provide an in‐depth analysis of NK cell populations in paediatric leukaemia patients. These results support the development of immunotherapies targeting immunosuppressive receptors, such as NKG2A, to enhance innate immunity against paediatric leukaemia.